2016
DOI: 10.1007/s10646-016-1714-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of cadmium and Microcystis aeruginosa (cyanobacterium) on the growth, antioxidative responses and accumulation of cadmium and microcystins in rice seedlings

Abstract: Cadmium pollution and harmful cyanobacterial blooms are two prominent environmental problems. The interactive effects of cadmium(II) and harmful cyanobacteria on rice seedlings remain unknown. In order to elucidate this issue, the interactive effects of cadmium(II) and Microcystis aeruginosa FACHB905 on the growth and antioxidant responses of rice seedling were investigated in this study, as well as the accumulation of cadmium(II) and microcystins. The results showed that the growth of rice seedlings was inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Cucumis sativus -protection against anthracnose (Colletotrichum orbiculare) via the induction of SAR [64] Chlorella oocystoides, Chlorella minutissima Zea mays -enhanced chlorophyll, P, and K content -improved biomass [65] Chlorella vulgaris Telfairia occidentalis -enhanced germination ratio -higher number of leaves and yield -improved chlorophyll, carbohydrates, proteins, and lipid content [66] Microcystis aeruginsa Oryza sativa -heavy metal (Cd) stress alleviation with decreased Cd accumulation, increased translocation of Cd from root to shoot, and enhanced dry weight [67] Nostoc sp.…”
Section: Chlorella Fuscamentioning
confidence: 99%
“…Cucumis sativus -protection against anthracnose (Colletotrichum orbiculare) via the induction of SAR [64] Chlorella oocystoides, Chlorella minutissima Zea mays -enhanced chlorophyll, P, and K content -improved biomass [65] Chlorella vulgaris Telfairia occidentalis -enhanced germination ratio -higher number of leaves and yield -improved chlorophyll, carbohydrates, proteins, and lipid content [66] Microcystis aeruginsa Oryza sativa -heavy metal (Cd) stress alleviation with decreased Cd accumulation, increased translocation of Cd from root to shoot, and enhanced dry weight [67] Nostoc sp.…”
Section: Chlorella Fuscamentioning
confidence: 99%
“…This mechanism may be suggested by the results in Figure 3a where the local cultivar (Nep cai hoa vang) grows closer to control values in the presence of 5 and 10 µmol/L Cd and may be therefore adapted to high Cd concentrations. Rice plants have been shown to develop trace metal protection mechanisms by sequestering metals in roots or by combining them with deprotonated organic acids, proteins, and polysaccharides [52]. For the 5 and 10 µmol/L Cd conditions, the results in Figure 3a show further a significant decrease in biomass for the Asia variety of 41% and 60% respectively with respect to the control at 0 µmol/L Cd.…”
Section: Effects Of CD Cu and Pb On Rice Plant Growthmentioning
confidence: 96%
“…Photosynthetic reactions involving photosystem II (PSII) have been proposed to be the principal target of Cu toxicity. In rice plants, Cu has been associated with the production of reactive oxygen species (ROS), leading to oxidative stress [52,55]. For sensitive plant species, such as local rice variety in Vietnam, 3.2 mg/kg (equivalent to 50 µmol/L Cu) were shown to be toxic, yielding decrease of about 10-20% in root biomass as shown in Figure 3b.…”
Section: Effects Of CD Cu and Pb On Rice Plant Growthmentioning
confidence: 99%
“…According to [ 66 ], the leaf weight of Spinacia oleracea decreases considerably after 21 days of MC exposure (50 and 100 µg/L). Numerous investigations have demonstrated that Oryza sativa roots, stems, and leaves exhibit increased biomass, surface area, and dry weight when exposed to low concentrations of MCs [ 67 , 68 , 69 ]. Exposure to increased concentrations of MC for 7 days had negative effects on the growth of rice plants, reflected in a decrease in the dry weight of roots, stems, and leaves, in addition to the inhibition of photosynthesis [ 70 ].…”
Section: Phytotoxicity Of MC On Crops In Hydroponic Systemsmentioning
confidence: 99%